Editing of PCNA Gene by CRISPR/Cas9 Technology to Improve the Red Chili Resistance to Yellow Leaf Curl Disease - Kurniawati, Devi Ayu; Suharsono, nFN; Santoso, Tri Joko (Jurnal AgroBiogen, 2020)
Yellow leaf curl disease caused by Pepper yellow leaf curl virus (PepYLCV), member of geminiviruses group, is responsible for heavy yield losses for chili pepper production. Resistant genes which can cause immunity to the disease have not been found in germplasm collection. The aim of the research was to edit proliferating cell nuclear antigen (PCNA) gene by using CRISPR/Cas9 technology for developing plant resistance against geminivirus in chili pepper. A CRISPR/Cas9 plasmid cassette construct harboring the guide RNA of PCNA gene was constructed by Golden Gate cloning strategy. The construct was then introduced into chili genome via in planta method using Agrobacterium tumefaciens EHA105. The transformed plants were bioassayed by virus inoculation and confirmed using PCR and DNA sequencing to identify a mutagenesis event in PCNA gene target. The results showed that CRISPR/Cas9 plasmid cassette harboring gRNA of PCNA gene was successfully constructed. In planta transformation using A. tumefaciens vector harboring CRISPR/Cas9-gRNA PCNA construct resulted in 307 and 193 transformed plants from chili var. Lingga and Ciko, respectively. Bioassay by using virus inoculation to the transformed plants obtained 6 and 14 lines of Lingga and Ciko, respectively, which were resistant to geminivirus (no symptom observed). The resistant lines of chili pepper var. Lingga and Ciko were mutated in PCNA gene with one base insertion or deletion mutation types. These results exhibit that the CRISPR/Cas9 genome editing can be used to induce mutant of PCNA gene in chili pepper. Further investigation is necessary to evaluate the selected chili lines resistant to PepYLCV infection.